PENGARUH MENSTRUASI TERHADAP AKTIVITAS OLAHRAGA SISWI DI SMP NEGERI 21 PALEMBANG - Ade Afni Utari (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The purpose of this study was to determine the effect of menstruation on sports activities. The research method was Ex post facto. Research samples were students who had experience in menstruation when the research is done. Sampling technique that used was purposive sampling. This data collection technique was Physical Freshness Test Indonesia. The data analysis technique used was t test, the result of the data obtained was analyzed by using quantitative analysis by calculating the difference between pretest and final test (Post-test). The results showed that: (1) Increased the average value of students from the first test to the final test; (2) testing by using t test obtained t count (2.82)> t-table (2.36); (3) There is influence of menstruation on student sport activity. Keywords— Menstruation, Sports Activities, Students